Conservation status and historical relatedness of South African communal indigenous goat populations using a genome-wide single-nucleotide polymorphism marker - Chokoe, T. C.; Hadebe, K.; Muchadeyi, F. C.; Nephawe, K. A.; Dzomba, E. F.; Mphahlele, T. D.; Matelele, T. C.; Mtileni, B. J. (Frontiers in Genetics, 2022)
Indigenous goats forms the majority of populations in smallholder; low input, low output production systems and are considered an important genetic resource due to their adaptability to different production environments and support communal farming. Effective population size (Ne), inbreeding levels, and the runs of homozygosity (ROHs) are effective tools for exploring the genetic diversity and understanding the demographic history in efforts to support breeding strategies to use and conserve genetic resources. Across populations, the current Ne of Gauteng was the lowest at 371 animals, while the historical Ne across populations suggests that the ancestor Ne has decreased by 53.86%, 44.58%, 42.16% and 41.16% in Free State (FS), North West (NW), Limpopo (LP) and Gauteng (GP), respectively, over the last 971 generations. Genomic inbreeding levels related to ancient kinship (FROH >5Mb) was highest in FS (0.08±0.09) and lowest for Eastern Cape (EC) (0.02±0.02). A total of 871 ROH island regions which include important environmental adaptation and hermo-tolerance genes such as IL10RB, IL23A, FGF9, IGF1, EGR1, MTOR and MAPK3 were identified (occurring in over 20% of the samples) in FS (n = 37), GP (n = 42), NW (n = 2) populations only. The mean length of ROH across populations was 7.76Mb and ranged from 1.61Mb KZN to 98.05Mb (GP and NW). Distribution of ROH according to their size showed that the majority (n = 1949) of the detected ROH were >5Mb in length than the other categories. Assuming two hypothetical ancestral populations, the population from KZN and LP are revealed, supporting PC 1. The genomes of KZN and LP shared an origin but have substantial admixture from the EC and NW populations. The findings revealed that the occurrence of high Ne and autozygosity varied largely across breeds in communal indigenous goat populations at recent and ancient events when a genome-wide SNP marker was used. The use of Illumina goat SNP50K BeadChip shows that there was a migration route of communal indigenous goat populations from LP of South Africa to the eastern areas of the KZN, that confirmed their historical relatedness and which coincide with the migration periods of the Bantu nation.